2012
DOI: 10.5194/acp-12-4555-2012
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble forecasting with a stochastic convective parametrization based on equilibrium statistics

Abstract: Abstract. The stochastic Plant-Craig scheme for deep convection was implemented in the COSMO mesoscale model and used for ensemble forecasting. Ensembles consisting of 100 48-h forecasts at 7 km horizontal resolution were generated for a 2000×2000 km domain covering central Europe. Forecasts were made for seven case studies characterized by different large-scale meteorological environments. Each 100 member ensemble consisted of 10 groups of 10 members, with each group driven by boundary and initial conditions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 38 publications
4
41
0
Order By: Relevance
“…semble members using the Plant-Craig scheme differ from each other more than for the strongly forced cases, where initial and boundary condition variability is relatively more important (Groenemeijer and Craig, 2012). Our result is similar to what was found by Kober et al (2015), where the Plant-Craig scheme was found to perform better than a non-stochastic scheme for a weakly forced case, and at low Figure 7.…”
Section: Separation Into Weakly and Strongly Forced Casessupporting
confidence: 81%
See 4 more Smart Citations
“…semble members using the Plant-Craig scheme differ from each other more than for the strongly forced cases, where initial and boundary condition variability is relatively more important (Groenemeijer and Craig, 2012). Our result is similar to what was found by Kober et al (2015), where the Plant-Craig scheme was found to perform better than a non-stochastic scheme for a weakly forced case, and at low Figure 7.…”
Section: Separation Into Weakly and Strongly Forced Casessupporting
confidence: 81%
“…The present study investigates the behaviour of the scheme in a trial of 34 forecasts with the MOGREPS-R ensemble, using a grid length of 24 km. The mass-flux variance produced by the PC scheme is inversely proportional to the grid box area being used, and so it is not obvious from the results of Groenemeijer and Craig (2012) whether the stochastic variations of PC will contribute significantly to variability within an ensemble system operating at the scales of MOGREPS-R. Nonetheless, MOGREPS-R has been shown, in common with most ensemble forecasting systems, to produce insufficient spread relative to its forecast error in precipitation (Tennant and Beare, 2013), suggesting that there is scope for the introduction of a stochastic convection parameterization to be able to improve its performance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations